Drainage Instabilities in Granular Materials: A New Biaxial Apparatus for Fluid Fingering and Solid Remodeling Detection - Al Nemer, Rana; Sciarra, Giulio; Réthoré, Julien (Frontiers in Physics, 2022)
In this paper, the effect of fluid fingering on the solid remodeling of a granular material during drainage phenomenon is investigated. A new biaxial apparatus, endowed with two transparent windows and adapted to unsaturated soils, is used to capture the effects of hydraulic instabilities on the mechanical response, by means of high resolution cameras. A specimen of (40 × 50 × 11) mm 3 , of Fontainebleau sand NE 34 initially saturated by water, is connected to a pressure-controlled gas source to inject the gas into the sample. During the injection phase, fluid instabilities are detected and filmed. Using imaging techniques, grain remodeling and strain localization due to the two-phase fluid flow are measured.